Augmented Reality (AR) Media to Stimulate Early Reading Skills in Early Childhood - Novianti, Rahmah; Pratiwi, Niken (JIV-Jurnal Ilmiah Visi, 2024)
Early reading skills are one of the important aspects of language development in early childhood. Early reading is the first stage where children learn to recognize letters, sounds, and words simply. This study aims to determine whether media-based augmented reality (AR) can stimulate early reading skills in children. This type of research is a development research using the ADDIE model. The methods used to collect was instruments. The location of the research was at Darul Hikmah Islamic Kindergarten, the research was conducted in August-September 2024. The results of the study showed that the early reading skills were 43%, after the use of AR-based media, children's early reading skills increased to 78%. Based on this, it can be concluded that using media-based AR can improve children's early reading skills. This research implies that teachers can use AR-based media in the learning process.